Sensorial marketing within consumer behavior: bibliometric analysis and future trends - Olga Maritza Rodríguez-Ulcuango; Cristian Oswaldo Guerra-Flores; Roberto Fabián Sánchez-Chávez; Gina Maricela Cedeño-Ávila (Cogent Business & Management)
This bibliometric analysis explores the evolution of sensory marketing within consumer behavior, analyzing 1,189 articles from Scopus and Web of Science databases from 1985 to 2024. Sensory marketing, engaging in all five senses, has become a vital band strategy significantly impacting consumer perceptions, decisions, and behaviors. The study emphasizes the dominance of the United States, with notable contributions from China, the United Kingdom, and France. Leading institutions such as The Ohio State University and The Hong Kong Polytechnic University have played crucial roles in this field. Thematic evolution reveals a shift from initial research on hospitality and neuroscience to current focuses on consumer behavior in digital commerce and the integration of emerging technologies like virtual reality, augmented reality, and artificial intelligence. This trend underscores the importance of immersive, personalized experiences in shaping consumer behavior and brand loyalty. The study also highlights a dual focus on understanding sensory stimuli’s impact on behavior and exploring their role in promoting sustainable consumption and corporate social responsibility. This study provides a comprehensive framework for understanding sensory marketing’s trajectory and offers practical insights for marketers, highlighting the strategic use of sensory elements to enhance consumer engagement and loyalty.